Mapping the Redox State of CHOP-Treated Non-Hodgkin’s Lymphoma Xenografts in Mice - Xu, He N. (Adv Exp Med Biol, 2013)
Drug treatment may alter the metabolism of cancer cells and may alter the mitochondrial redox state. Using the redox scanner that collects the fluorescence signals from both the oxidized flavoproteins (Fp) and the reduced form of nicotin-amide adenine dinucleotide (NADH) in snap-frozen tumor tissues, we investigated the effects of chemotherapy on mouse xenografts of a human diffuse large B-cell lymphoma cell line (DLCL2). The mice in the treatment group were treated with CHOP – cyclophosphamide (C) + hydroxydoxorubicin (H) + Oncovin (O) + prednisone (P) using the following regimen: CHO administration on day 1 followed by prednisone administration on day 1–5. On day 5 the mitochondrial redox state of the treated group was slightly more reduced than that of the control group (p = 0.049), and the Fp content of the treated group was significantly decreased (p = 0.033).